Penerapan Latihan Intradialitik terhadap Adekuasi Hemodialisis: Literature Review - Isnah Ariyanti; Riri Maria; Masfuri Masfuri (FORIKES, 2021)
Hemodialysis patients were mostly physically inactive and their functional capacity had been reduced, even though exercise could improve physical fitness, aerobic capacity, quality of life, decrease depressive symptoms and include dialysis adequacy (measured as Kt/V). A lower Kt/V value means that the patient had inadequate HD, can lead to increased hospitalization time and costs, increased morbidity and mortality and should therefore be avoided. This study aims to determine the application of intradialytic exercise to hemodialysis adequacy. The method used in this study was literature review with electronic searches on 4 online databases: Wiley Online, Sciencedirect, clinical key and EBSCOhost (Medline and CINAHL plus). The keywords used were